Effective low-density lipoprotein-lowering therapy: Implementation in clinical practice. (29th August 2020) - Sinning, David; Landmesser, Ulf
Abstract: Although age-adjusted mortality of coronary heart disease has been successfully reduced over recent years, coronary heart disease still represents a leading cause of death and morbidity, in particular in patients at very high cardiovascular risk. Dyslipidaemia plays a major and causal role in the development and clinical progression of coronary heart disease. At present, low-density lipoprotein cholesterol represents the primary target of lipid-directed therapies for the prevention of cardiovascular disease and events. The new European guidelines recommend intensive statin therapy and the possible addition of ezetimibe to reduce low-density lipoprotein cholesterol to a goal of less than 1.8 mmol/L (<70 mg/dL) or by at least 50% if the baseline low-density lipoprotein cholesterol is between 1.8 and 3.5 mmol/L (70–135 mg/dL) in patients at very high cardiovascular risk. Also, the new European guidelines now mention the potential use of proprotein convertase subtilisin-kexin type 9 (PCSK9) inhibitors in very high-risk patients with persistently high levels of low-density lipoprotein cholesterol despite maximally tolerated statin treatment in combination with ezetimibe or in patients with statin intolerance. A recent European consensus document discusses the practical clinical use of PCSK9 inhibitors and provides more detailed recommendations. However, despite the overwhelming scientific evidence of the beneficial effects of lipid-lowering therapies, a large proportion of patients at very high cardiovascular risk are not treated according to the current European guideline recommendations. Reinforcing lipid-lowering therapies provides an excellent chance effectively to reduce morbidity and mortality from coronary heart disease.